THE EFFECTIVENESS OF PROBLEM-BASED LEARNING BASED ON SOCIO-SCIENTIFIC ISSUES ON STUDENTS' CRITICAL THINKING: A SYSTEMATIC LITERATURE REVIEW - Fatimah, Siti; Rahayu, Yuni Sri; Raharjo, Raharjo (JURNAL EDUSCIENCE, 2025)
Purpose– This study aims to analyze the impact of learning using the Socio-Scientific Issues (SSI)-based Problem-Based Learning (PBL) model on students' critical thinking skills in biology. Although various studies have examined PBL and SSI separately, there has not yet been a comprehensive study that summarizes the combined effectiveness of the PBL-SSI model and maps the development of research in this field. This study fills this gap through a systematic analysis of the latest empirical findings.Methodology – This study employed the Systematic Literature Review (SLR) method, adhering to the PRISMA guidelines. The articles analyzed were 35 indexed articles published between 2019 and 2024 with the keywords 'Problem-Based Learning (PBL)', 'Socio-Scientific Issues (SSI)', and 'Critical Thinking'. VOSviewer was used to map related keywords, followed by qualitative analysis.Findings – The study's results indicate that approximately 80% of studies report a significant improvement in students' critical thinking skills following the application of the PBL-SSI model. Environmental topics such as pollution, climate change, and renewable energy are the most dominant themes due to their relevance and authenticity. Bibliometric analysis also confirms a strong correlation between the keywords "PBL," "SSI," and "Critical Thinking," indicating growing scientific interest in this integrated learning model. The correlation between PBL and SSI is more pronounced than the application of either one alone, as it enables students to solve real-world problems actively, considering both scientific and social aspects.Contribution –These findings have practical implications for educators, including the development of authentic teaching materials and the integration of fundamental social and environmental issues into the learning process.